Optimization Design of Multiphase Interleaved DC-DC Boost Converter - Ponniran, Asmarashid (International Journal of Integrated Engineering, 2019)
This paper discusses the optimization design of multiphase interleaved DC-DC boost converter (IBC) in order to achieve current stress and current ripple reductions. 1-phase (conventional), 2-phase, and 3-phase IBCs are considered in this study. Multiphase is defined as multiple parallel branches of circuit of the converter, while interleaved means all branches are operate in phase-shifted to each other in the same frequency and duty cycle. All IBC structures are analyzed with consideration of semiconductor loss, conduction loss, current stress, and input current ripple. Conventional and multiphase IBCs are analyzed in term of optimizing the converter design which are 1-phase, 2-phase, and 3-phase IBCs. The results show that by increasing number of phases from 1 to 3, the power losses are reduced to 60%, 40%, and 20%, respectively. Meanwhile, the input current ripple is reduced to 0.3 A, 0.2 A, and 0.1 A, respectively. Thus, with the prescribed considerations, 2-phase IBC is selected as the optimized design of multiphase IBC.